Agrobacterium Protocols (Volume 2) - Kan, Wang (Humana Press, 2015)
Agrobacterium tumefaciens is a soil bacterium that for more than a century has been known as a pathogen causing the plant crown gall disease. Unlike many other pathogens, Agrobacterium is able to deliver DNA to plant cells and permanently alter the plant genome. The discovery of this unique feature has provided plant scientists with a powerful tool to genetically transform plants for both basic research purposes and for agricultural advancement...